2016
DOI: 10.1016/j.physd.2015.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Simple model of cell crawling

Abstract: Based on symmetry consideration of migration and shape deformations, we formulate phenomenologically the dynamics of cell crawling in two dimensions. Forces are introduced to change the cell shape. The shape deformations induce migration of the cell on a substrate. For time-independent forces we show that not only a stationary motion but also a limit cycle oscillation of the migration velocity and the shape occurs as a result of nonlinear coupling between different deformation modes. Time-dependent forces are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 37 publications
(91 reference statements)
1
34
1
Order By: Relevance
“…It is now understood that the shape of cells can be highly variable and has a strong influence on their collective behavior [36,[60][61][62][63][64][65]. In our previous work, we showed that the present model exhibits an alignment transition in coherent migration as a function of cell shape [47].…”
Section: Influence Of Cell Shapementioning
confidence: 70%
“…It is now understood that the shape of cells can be highly variable and has a strong influence on their collective behavior [36,[60][61][62][63][64][65]. In our previous work, we showed that the present model exhibits an alignment transition in coherent migration as a function of cell shape [47].…”
Section: Influence Of Cell Shapementioning
confidence: 70%
“…This is perhaps most explicitly modeled in the minimal approach of Ohta et al [122], who study the dynamics of a deformable self-propelled particle, and have later extended this to describing the dynamics of Dictyostelium cells [123]. In the simplest version of their model, cells are described by a velocity v and a single tensor variable S ij indicating the cell’s shape deformation from a circle [122]; the most general equations of motion coupling v and S ij to a given order can then be written down.…”
Section: What Is a Collective Cell Motility Model? Basic Elements mentioning
confidence: 99%
“…For this purpose, we replace eqs. (20) and (22) by constant values for the active velocity and shape deformation, as explained shortly. In order to highlight the effect of the Poiseuille flow, we do not consider the interaction with the boundary explicitly in this section.…”
Section: Rigid Active Particlesmentioning
confidence: 99%
“…The other is the time-derivative term of the active velocity in eq. (20). Note that this inertia-like term is also derived from the Stokes equation for an active droplet on the interface of which a chemical reaction takes place to change the local surface tension [91,92].…”
Section: Overdamped Limitmentioning
confidence: 99%
See 1 more Smart Citation